Evidence for increased microglial priming and macrophage recruitment in the dorsal anterior cingulate white matter of depressed suicides - Torres-Platas, Susana G.; Cruceanu, Cristiana; Chen, Gary Gang; Turecki, Gustavo; Mechawar, Naguib (Brain, behavior, and immunity, 2014)
Despite increasing evidence supporting the neuroinflammatory theory of depression, little is known about cerebral macrophages in individuals suffering from major depression. In the present study, we investigated the morphology and distribution of cells immunostained for the macrophage-specific marker ionized calcium binding adaptor molecule 1 (IBA1) in the dorsal anterior cingulate cortex (dACC) white matter of middle-aged depressed suicides and matched non-psychiatric controls. This region is known for its implication in mood disorders, and its white matter compartment was previously found to display hypertrophic astrocytes in depressed suicides. Distributions of IBA1-immunoreactive (IBA-IR) microglial phenotypes were assessed using stereology and cell morphometry, and blood vessels were characterized as being intimately associated with either a high or a low density of IBA1-IR amoeboid-like cells. Total densities of IBA1-IR microglia did not differ between depressed suicides and controls. However, a finer analysis examining relative proportions of microglial phenotypes revealed that the ratio of primed over ramified (“resting”) microglia was significantly increased in depressed suicides. Strikingly, the proportion of blood vessels surrounded by a high density of macrophages was more than twice higher in depressed suicides than in controls, and this difference was strongly significant. Consistent with these observations, gene expression of IBA1 and MCP-1, a chemokine involved in the recruitment of circulating monocytes, was significantly upregulated in depressed suicides. Furthermore, mRNA for CD45, a marker enriched in perivascular macrophages, was also significantly increased in samples from depressed suicides. An increase compared to controls was also observed in the proportion of blood vessels surrounded by a high density of CD45-IR cells, but this difference did not reach significance. These histological and molecular data suggest the recruitment of monocytes in dACC white matter of depressed suicides, although it cannot be excluded that other types of macrophages (including microglia) account for the observed accumulation of macrophages closely associated with blood vessels. Altogether, these findings suggest that the previously reported depression- and suicide-associated increases in circulating pro-inflammatory cytokines may be associated with low-grade cerebral neuroinflammation involving the recruitment of circulating monocytes.